The Influence of Busy Book Media on the Language Development of Children Aged 5-6 Years - Alvi Durrotin Arfiah; Mustafa Hamed Mohamed Alehirish (HADHANATUNA: Journal of Early Childhood Education, 2025)
The use of instructional media in early childhood education plays a pivotal role insupporting children’s language development, particularly during the preoperational stagewhen symbolic thinking and emergent literacy skills begin to form. Busy Book media servesas an effective pedagogical tool that enables teachers to introduce letters, facilitatephonemic awareness, and guide children in constructing simple words through engaging,hands-on activities. Its interactive and tactile nature enhances children’s intrinsicmotivation, reducing feelings of boredom and promoting sustained attention throughoutthe learning process. In implementing the Busy Book intervention, the lesson plan (RPP)was adapted to align with the thematic unit on transportation, specifically focusing on twowheeled vehicles such as bicycles. Findings from hypothesis testing indicate a significantinfluence of Busy Book media on the language development of children aged 5–6 years atMutiara Bunda Kindergarten, Bogo Nganjuk. The average N-Gain score of theexperimental group reached 95.00%, demonstrating high effectiveness, while the controlgroup achieved 64.29%, categorized as moderately effective. Furthermore, the effect sizeanalysis revealed that Busy Book media contributed to a 62.22% improvement in children’slanguage development outcomes, underscoring its substantial impact as a developmentallyappropriate language-learning resource